Optimization of Product Knowledge In Improving The Storytelling Skills of Songke Weaving MSME - Berybe, Gregorius; Yulin, Floriana (Publication Division of International Ecsis Association, 2023)
Product Knowledge is an important aspect of understanding the characteristics, benefits, and value of products. In the context of Songke Weaving, knowledge includes history, motifs, materials, and manufacturing processes. This study aims to measure the level of product knowledge of Songke Weaving MSME actors in Batu Cermin Tourism Village and make a description guide to improve storytelling skills in detail. This study used a qualitative descriptive approach. Data was collected through interviews, observation, and documentation. The participants of the study were Songke Weaving MSME actors. The results of the research of most Songke Weaving MSME actors in Batu Cermin Village have limited product knowledge, especially related to history, manufacturing processes, and benefits. However, a better understanding of the motives, and benefits of the product. The manufacturing process of Songke Weaving was previously done naturally but took longer, the quality of Songke Weaving today is affected by changes in the manufacturing process. This research also highlights the functional, and emotional benefits of Songke Weaving for the people of Manggarai. Improvement efforts through product description guidelines can help increase product value for consumers, and support the development of MSMEs in Batu Cermin village.